Pathological characteristics and predictive factors of prostate biopsy in patients with serum PSA levels between 0 and 4.0 ng/ml - Su, Rui; Pan, Jin-feng; Ren, Da-wei; Jiang, Jun-hui; Ma, Qi (Frontiers in Oncology, 2022)
Background: This study aimed to analyze the pathological characteristics and predictive factors of prostate biopsy in men with PSA levels below 4.0 ng/mL. Patients and Methods: We retrospectively analyzed 158 patients underwent prostate biopsy with PSA levels below 4.0ng/mL. Pathological results were statistically analyzed. The logistic regression analysis was used to determine the predictive factors for malignant outcome. Subgroup analysis was performed on patients who received surgery and the postoperative pathological upgrading was counted. Results: A total of 143 patients were enrolled. The tumor detection rate was 20.3%. Among these patients, most of them (79.3%) were prostate adenocarcinoma, but rare malignant tumors also accounted for 20.7%. Logistic regression analysis indicated that the only independent predictive factor for a positive prostate biopsy was PI-RADS score. For prostate adenocarcinoma cases, 95.7% of them were organ localized and 47.8% cases were clinically significant. Subgroup analysis was performed on 14 patients who received surgical treatment. 28.6% of patients were upgraded to clinically significant prostate cancer, while 64.3% of patients had an upgrade of tumor stage. Conclusion: Our study indicated that 20.3% male with PSA levels between 0 and 4.0 ng/mL were diagnosed as prostate malignancies. Among these patients, most of them (79.3%) were diagnosed as prostate adenocarcinoma, and several uncommon types of malignancies were also detected in 20.7% patients. The only risk factor for a positive biopsy in patients with low PSA concentration was PI-RADS score. It should be emphasized that the invasiveness of PCa patients diagnosed by biopsy may be underestimated as more than half of patients will upgrade their Gleason Score or clinical stages after surgery. Thus, it should be paid more attention by clinicians to patients with PSA between 0-4.0ng/mL.